Pengayaan Literatur dan Implementasi Nilai Pancasila pada Anak Usia Dini di SDN Suci 5 Jember - Wardhono, Adhitya; Qori’ah, Ciplis Gema; Nasir, M Abd; Puspito, Agung Nugroho; Yoniksa K, Bintang; Rahmadini, Intan Aulia; Lestari, Ria Nova Agustin Puji; Laela, Intan; Ningsih, Arumiyati; Thaka, Ichan Ryan; Prakoso, Bhim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Introducing Pancasila from an early age is crucial to fostering a sense of love for the homeland, starting with education at the primary school level. This socialization activity was conducted by university students at SDN Suci 5, located in Desa Suci, Kecamatan Panti, Kabupaten Jember, due to many students lacking an understanding of the importance of learning Pancasila. The goal of this socialization is to help students internalize and apply the values of Pancasila in their daily lives, considering that Pancasila is the foundation of Indonesia, a multicultural nation characterized by diverse ethnicities, races, religions, and cultures. This diversity is reflected in Pancasila's motto,